PENGARUH FREKUENSI PERTEMUAN KOMITE AUDIT, UKURAN KOMUTE AUDIT, UKURAN KANTOR AKUNTAN PUBLIK, DAN AUDIT TENURE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris Pada Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Anggraini Tiara; Surya Adri Satriawan Raja; Aunurrafiq Aunurrafiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of audit committee meeting frequency, audit committee size, audit firm size, and audit tenure on Corporate Social Responsibility disclosure. The population of this study is the consumer goods industry companies listed on the Indonesian Stock Exchange from 2014 to 2018. The sampling technique used the purposive sampling method and acquired 26 companies with 130 units of observations. This study tested the hypothesis using multiple regression analysis. The results of this study indicate that there is a positive effect of the audit committee size, audit firm size, and audit tenure on Corporate Social Responsibility disclosure. Meanwhile, the audit committee meeting frequency has no effect on Corporate Social Responsibility disclosure. The test results of the coefficient of determination in this study were 0.3371 or 33.71%. This means that the independent variable is only able to explain the dependent variable CSR disclosure of 33.71%, while the rest is explained by other variables outside the research model.Keyword : Audit Committee Meeting Frequency, Audit Committee Size, Audit Firm Size, Audit Tenure, Corporate Social Responsibility Disclosure